Characteristics of pediatric emergency department visits for youth 10-15 years old with injuries due to interpersonal violence. Issue 1 (2nd January 2022) - Ryan, Leticia Manning; Irvin, Nathan; Miller, Mattea; Walter, Creason; Jones, Vanya
Abstract: This retrospective cohort study at an urban academic pediatric emergency department (ED) in the United States identified all visits for youth 10-15 years of age for injury due to intentional interpersonal violence between January 2019 and December 2020. Demographic and clinical data were abstracted, including circumstances of the event. Data analysis included a comparison of pre-pandemic visits to pandemic visits after a statewide stay-at-home order was issued (March 30, 2020). Of 2780 10-15 year old youth evaluated for any injury, 819 (29.5%) had intentional/violence-related injuries. Most patients were male (53.1%), Black/African-American (84.1%), and were enrolled in a public insurance plan (75.0%). Although peer-violence related injuries comprised a substantial proportion (19.2%), the majority resulted from family violence (54.7%), which may include child maltreatment or physical fighting. Most injuries occurred at home (53.9%). Alcohol, drugs and weapons were significantly more likely to be involved in violent events during the pandemic in comparison to pre-pandemic (12.5 vs 5.0%, 11.4% vs 3.0%, 30.4% vs 8.5%; p < 0.001). Our findings support the need for ED-based efforts to screen and intervene for family and peer violence and other contributory factors (including personal, family and peer alcohol, drug and weapons access) when youth present with intentional injuries, which can be critical to preventing future violence.